Detection of seedborne fungi in Stylosanthes guianensis, S. hamata, and S. scabra - Nan, Z.B.; Hanson, Jean (1998)
The effects of pretreatment with sodium hypochlorite and plating onto potato dextrose agar, oatmeal agar, water agar and blotter of the range and incidence of fungi isolated from seeds of Stylosanthes species were studied. A survey was made of the fungi associated with 39 seed lots of S. guianensis, 25 lots of S. hamata, and 14 lots of S. scabra. Oatmeal agar with seed pretreatment was the most suitable method. The most frequently isolated fungi were Phoma glomerata, Rhizoctonia solani, Fusarium oxysporum, Alternaria alternata, Cladosporium cladosporioides and Penicillium species. Variation in incidence and species of seedborne fungi was observed among the three Stylosanthes species tested. Hard seed of S. hamata had a much lower incidence of seedborne fungi than other seed. The majority of fungi were isolated from the seed coat. Only a small percentage of infection was found in the seed endosperm. The pathogenicity test showed that all 78 isolates of 27 fungal species tested reduced the length of seedlings growing on water agar surface; where as Colletotrichum truncatum, C. gloeosporioides, Fusarium oxysporum, F. avenaceum, Botrytis cinerea, Rhizoctonia salani and F. acuminatum killed most of the test seedlings.